2018
DOI: 10.1002/ppap.201800087
|View full text |Cite
|
Sign up to set email alerts
|

Non‐oxidative methane coupling to C2 hydrocarbons in a microwave plasma reactor

Abstract: Non‐oxidative methane activation is carried out in a microwave plasma reactor for coupling to higher hydrocarbons. Fourier transform infrared spectroscopy (FTIR) was used to measure absolute concentrations of the major hydrocarbon species. Hydrogen concentration was also independently inferred from pressure‐based change in molar flow measurements. By closing both the carbon and hydrogen balance, from stoichiometry of the reactions, the amount of deposits was obtained as well. Additionally, core gas temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 47 publications
(55 reference statements)
3
42
0
Order By: Relevance
“…The rotation temperature was 1,800 K, which was sufficient for the pyrolysis. Many research works confirmed that warm plasmas, such as spark discharge, MW, and GA, are dominated by the thermal reactions rather than the electron collision reactions …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rotation temperature was 1,800 K, which was sufficient for the pyrolysis. Many research works confirmed that warm plasmas, such as spark discharge, MW, and GA, are dominated by the thermal reactions rather than the electron collision reactions …”
Section: Resultsmentioning
confidence: 99%
“…Many research works confirmed that warm plasmas, such as spark discharge, MW, and GA, are dominated by the thermal reactions rather than the electron collision reactions. [44][45][46] The temporal evolution (2 ns/5 ns) of the OES in filamentary discharge were investigated to obtain further insight into the chemical processes. Figure 10a illustrates the time variation of the emission intensities of CH(A-X) and C 2 (516 nm) along the current in the filamentary discharge.…”
Section: Gas Temperaturementioning
confidence: 99%
“…Furthermore, the coke production under conventional heating was double of that obtained under MW heating [128]. In addition, Minea et al tested a microwave plasma reactor for the MNOC, detecting at low gas temperatures, ethane selectivities up to 60% due to plasma chemistry while, at higher temperatures, the thermal effect became greater leading to the formation of acetylene and deposits [129]. In more recent times, Julian et al, continued their studies on the non-oxidative coupling of methane performed using a Mo/ZSM-5@SiC structured catalyst [130].…”
Section: Of 58mentioning
confidence: 99%
“…Consequently, Therefore, it seems possible that the inorganic material in the producer gas was melted in the plasma core and deposited on the cooler walls of the quartz tube. The problem of deposit interfering with the microwaves transfer and plasma stability is a common issue in the MWP processing of carbon sources [42,51]. Finally, another important factor that may have caused a difference in the conversion rate could have been connected with the hydrogen concentration.…”
Section: Comparison Of the Simulated And The Sewage Sludge-derived Prmentioning
confidence: 99%